Impact of Domestic Investment, Market Size, and Trade Openness on Outward FDI: A Panel Data Analysis on BRICS - Mathad, Kavita; Kumar, D. N. S. (Indian Journal of Finance, 2019)
The recent phenomenal increase in the outward foreign direct investment (FDI) of emerging countries has raised concerns among policymakers. One school of thought argues that when multinational firms relocate production facilities abroad, it reduces the likelihood of concurrent investments in the home country, resulting in reduced domestic output. In this case, the outward FDI would harm the domestic investments. The other argues that the outward FDI would be more advantageous for the domestic investment when firms internationalize for entering into new markets and/or to import intermediate goods, wherein outward investments boost the returns in the home country, leading to a positive impact of outward FDI on domestic investment. The influence of the outward FDI on the domestic investment of any country or a region state cannot be generalized as each country is unique, and the drivers of investments would differ for different countries at the different development phases of each country. An attempt was made in this study to empirically trace the impact of the domestic investment, market size, and trade openness of the BRICS’s members on the BRICS’s outward FDI as a group. The results of the panel least square method highlighted that the variables - domestic investment and trade openness of BRICS had a positive effect on the outward FDI ; whereas, the market size of BRICS was inversely related to outward FDI of BRICS. The data were tested for stationarity and Hausman test validated the results.